Linguistic boundaries in the lowland of the Ecuadorian Pacific. Third Part Abstract - Gómez Rendón, Jorge (Centro de Publicaciones Pontificia Universidad Católica del Ecuador, 2021)
The present article expands on the analysis offered in previous contributions of ethno-historicand onomastic evidence of the languages of the Ecuadorian coast at the beginning of the Spanishconquest. Unlike in previous contributions, it references both the systematization and onomasticdata analysis published in ethno-historic and ethnolinguistic compilations in order to complimentthe information and compare available resources. To do this an onomastic study in some zonesof the territory assigned to Manteño-Huancavilca culture is referred to. The results of thestudy confirm the presence of a Barbacoano or “Colorado” linguistic substratum in the southcentral of the coastline and its immediate hinterland, which in some cases appears mixed with theEsmeraldeña (non-classified) language’s onomastics and a linguistic entity related to the Puruha-Cañari culture. The Babarcoano migration model allows the interpretation of the results of thiswork and of previous contributions in a coherent manner, however provisionally, leaving pendingfor future research the rescue and analysis of pre-Hispanic onomastics that reside in archivesand in the oral memory of communities.